Method for establishing the multipath adaptive mitigation model considering deformation displacement of monitoring stations - Guo Zihuai; Yibin Yao; Chaoqian Xu; Mingxian Hu (Geo-spatial Information Science, 2024)
Multipath effects are an unavoidable error in Global Navigation Satellite System (GNSS) deformation monitoring. Existing multipath models are predominantly established under stationary conditions and are not applicable to scenarios involving slope ruptures or rapid displacements. To address this issue, we propose the Multipath Adaptive Mitigation Model (MAMM) and validate its precision. The study demonstrates that traditional multipath models are ineffective in suppressing multipath errors under the specified conditions. The comparison between MAMM and the Multipath Hemispherical Model (MHM) indicates that, in the simulated displacement experiments, MHM’s effectiveness in mitigating multipath errors significantly decreases as the actual displacement distance increases, whereas MAMM consistently maintains an improvement rate in positioning precision of over 100%, markedly surpassing that of MHM. In real displacement scenarios, MAMM demonstrates similar advantages to those observed in the simulated experiments under instantaneous deformation conditions, while in slow displacement scenarios, MAMM offers a limited precision advantage over MHM.